Snappy style paper decoration creations - Phillips, Jennifer; Paper work (North Mankato, Minn Capstone Press, 2013)
The best decorations show your personal taste and your personal skill. Sculpt paper into crazy quilts, adorable animals, and other gorgeous decorations that will brighten any room
A gift from book Africa
Handcrafts
1 2 13 15
NEW_ZTN_GN
Keywords: Handicraft; Paper work